Bowel Obstruction due to Meckel’s Diverticulum : A Case Report (Global Journal of Medical Research, 2023)
Meckel s diverticulum is the most prevalent congenital abnormality of the gastrointestinal tract This anomaly is due to the incomplete obliteration of the omphalomesenteric duct during the 7th week of gestation and is classically located 2 feet proximal to the ileocecal valve 1 While most of the population may be asymptomatic clinical manifestation including gastrointestinal bleed and intestinal obstruction can emerge Despite the frequency of Meckel s diverticulum it is commonly misdiagnosed due to its mimicry of appendicitis We reported in our case a patient with bowel obstruction Meckel s divertiulum was discovered during surgery
Keywords: meckel’s diverticulum; bowel obstruction